2022
DOI: 10.1371/journal.pgph.0000707
|View full text |Cite
|
Sign up to set email alerts
|

The links of fine airborne particulate matter exposure to occurrence of cardiovascular and metabolic diseases in Michigan, USA

Abstract: Air pollutants, particularly airborne particulate matter with aerodynamic diameter < 2.5μm (PM2.5), have been linked to the increase in mortality and morbidity associated with cardiovascular and metabolic diseases. In this study, we investigated the dose-risk relationships between PM2.5 concentrations and occurrences of cardiovascular and metabolic diseases as well as the confounding socioeconomic factors in Michigan, USA, where PM2.5 levels are generally considered acceptable. Multivariate linear regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…A Syntax score of I was calculated based on the calculator available at https:// syntaxscore.org/calculator/syntaxscore/frameset.htm (accessed on 1 December 2023) (Syntax Score calculator 1, version 2. 28,2022).…”
Section: Patients' Study Groupmentioning
confidence: 99%
“…A Syntax score of I was calculated based on the calculator available at https:// syntaxscore.org/calculator/syntaxscore/frameset.htm (accessed on 1 December 2023) (Syntax Score calculator 1, version 2. 28,2022).…”
Section: Patients' Study Groupmentioning
confidence: 99%
“…Fernandes et al 3 suggested an increase in the frequency and severity of seizures in epilepsy patients due to high air pollution, with particles entering the body causing inammation. Airborne wear particles are also linked to cardiovascular and metabolic diseases, 4 diabetes, 5 and cancer, [6][7][8] and have been estimated to have contributed to 5 million deaths worldwide. 9 To mitigate these problems, new regulations have been introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies and biomedical research have consistently linked real-world airborne pollutants to the increase of mortality and morbidity associated with modern human complex diseases. [1][2][3][4][5] In particular, environmental airborne particulate matter in fine and ultrafine ranges (aerodynamic diameter <2.5 µm, PM 2.5 ) is strongly associated with the development of air pollution-associated systemic diseases (figure 1). 1 5 6 There exist linear dose-risk relationships between PM 2.5 concentrations and the occurrence of cardiovascular and metabolic diseases, as a 3% increase in cardiovascular disease incidence or a 1% increase in diabetes prevalence was observed in populations under 10 µg/m 3 increase in PM 2.5 exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic PM 2.5 exposure increases the danger of cardiovascular and metabolic diseases to an even greater degree and effects may be more pronounced in susceptible populations such as older adults, lower socioeconomic status and individuals with pre-existing conditions. 4 Short-term exposure to polluted air at levels generally considered 'acceptable' may impair mental ability in elderly people in the USA. 7 In most cases, airborne PM 2.5 is a complex mixture of particles and gases from gasoline and diesel engines, mixed with dust from wear of road surfaces and tires.…”
Section: Introductionmentioning
confidence: 99%